Rancang Bangun Alat Pendeteksi Tingkat Stress Pada Manusia Berbasis Arduino Uno - Hidayah, Nuril; Mujur Rose, Martinus; Nasron, Nasron (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
Stress can be sourced from a variety of things, many negative impacts without us realizing that stress is caused by health.Therefore, a tool capable of being used to automatically measure stress levels in humans is required as a tool to monitor health. This human stress level detection tool uses a tool used to measure the level of human tension condition with three parameters, namely measuring heart rate using pulse sensor, body temperature using temperature sensor DS18B20 and skin moisture using galvanic skin response (gsr) sensor then the data will be sent, processed and processed using Arduino Uno R3 Microcontroller to process information to determine the level of stress condition of a person classified into 4 conditions namely relax , calm, anxious, and tense. Data retrieval is done for 1 minute with the measurement data results displayed on the LCD monitor scree